1986
DOI: 10.1590/s0373-55241986000100003
|View full text |Cite
|
Sign up to set email alerts
|

Características físicas e químicas do sistema estuarino-lagunar de Cananéia-Iguape

Abstract: Synopsis This paper reports a series of data on saZinity~ current~ nutrient and dissoZved oxygen concentration observed in the Cananéia-Iguape region. The circuZation of the system is dominated by tides entering from Barra de Cananéia and Barra de Icapara. Due to differenoes in the ebb and fZood periods in Mar de CananE~ia and Mar do Cubatão, residuaZ fZows of opposite directions were observed in the bottom Zayers of these channeZs. Observations from January 1982 in Mar de Cananéia showed nutrient concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
37

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 1 publication
0
15
0
37
Order By: Relevance
“…Although located 40 km from Trapandé Bay, the Valo Grande Channel influences nutrient cycling in the southern sector of the Cananeia-Iguape system. MIYAO et al (1986) observed higher concentrations of phosphates in the mouth region of the Trapandé Bay that were caused by the resuspension of sediments at the tide entrance. JORCIN (2000) found higher concentrations of total phosphorus and nitrogen in the Cananeia region during the summer, in areas coinciding with the region of transects 8 and 9 that were associated with a seasonal increase in the levels of organic matter.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Although located 40 km from Trapandé Bay, the Valo Grande Channel influences nutrient cycling in the southern sector of the Cananeia-Iguape system. MIYAO et al (1986) observed higher concentrations of phosphates in the mouth region of the Trapandé Bay that were caused by the resuspension of sediments at the tide entrance. JORCIN (2000) found higher concentrations of total phosphorus and nitrogen in the Cananeia region during the summer, in areas coinciding with the region of transects 8 and 9 that were associated with a seasonal increase in the levels of organic matter.…”
Section: Discussionmentioning
confidence: 82%
“…The outer region presented the highest faunal differences between campaigns, presumably due to the powerful hydrodynamic effects generated by interactions with the Cananeia Sea and the Icapará Inlet. This region has strong, dynamic currents near its bottom (>1.0 m/s) due to the influence of the mouth of the Cananeia Sea and the Icapará Inlet (MIYAO et al 1986), as well as the constriction of the lagoon channels (KUTNER 1962, TESSLER & SOUZA 1998. The friction stress caused by the bottom currents tends to resuspend fine sediments, nutrients and organic matter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O aporte do RI também declinou generalizadamente a salinidade média no ECI, sobretudo nas margens e no pelagial (GEOBRÁS 1966;DAEE, 2011). Com base no período em que o VG esteve fechado ( Miyao et al, 1989), supõe-se que as condições límnicas no ECI precedentes ao VG eram raras e se davam ocasionalmente com excepcionais elevações da descarga no período chuvoso. Sob a ação do VG, tal condição é praticamente persistente nas imediações do VG DAEE, 2011;Barrera-Alba et al, 2007;Barrera-Alba et al, 2009).…”
Section: Caracterização Ambiental Do Eciunclassified
“…Para minimizar tais prejuízos, o VG foi completamente obstruído em 1978 . Após a obstrução do VG, no eixo sul, a salinidade média superficial elevou-se, em média, de 21.7 para 28.5 e a de fundo de 28 para 33; já, nas imediações do VG, a elevação salina foi ainda mais proeminente, passando, em média, de 0 a 20, no pelagial, e de 2.1 à 20 no fundo (GEOBRÀS, 1966;Miyao et al, 1989;Bonetti-Filho & Miranda, 1997;Barreira-Alba et al, 2009). Porém, a perda da competência do leito original do RI, associado ao fechamento completo do VG, causou enchentes sucessivas e severas em áreas rurais e urbanas da cidade de Iguape nos períodos chuvosos (Mahiques et al, 2012).…”
Section: Histórico E Impacto Ambiental Do Vg No Eciunclassified